2008
DOI: 10.1007/bf03003074
|View full text |Cite
|
Sign up to set email alerts
|

Work family balance, stress, and salivary cortisol in men and women academic physicians

Abstract: With increasing responsibility at home, women and men reacted differently with regard to cortisol responses over the day. However, in the evening, controlling for the morning cortisol, these gender differences were not as obvious. These findings highlight traditional gender patterns among both women and men physicians in the challenge of finding a balance between work and family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…The significant relationship between work-family conflict and emotional exhaustion indicate that physicians who experience greater conflict resulting from performing both work and family roles tend to experience greater emotional exhaustion. Similar results were obtained by (Ray and Miller, 1994;Baron and Kenny, 1986a;Bergman et al, 2008;Fu and Shaffer, 2001;Houkes et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…The significant relationship between work-family conflict and emotional exhaustion indicate that physicians who experience greater conflict resulting from performing both work and family roles tend to experience greater emotional exhaustion. Similar results were obtained by (Ray and Miller, 1994;Baron and Kenny, 1986a;Bergman et al, 2008;Fu and Shaffer, 2001;Houkes et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…A study by Burke and Greenglass (2001) and Sweeney and Summers (2002) on nursing staff during hospital restructuring has shown that increased job burnout is an important consequence of work-family conflict. A longitudinal study of individuals from eight occupational groups including physicians revealed that increased levels of work-family conflict results in higher levels of burnout including emotional exhaustion (Baron and Kenny, 1986a;Bergman et al, 2008). Similar results have been reported by Peiro et al (2001) (Fu and Shaffer, 2001) among health care professionals, Lingard and Francis (2006) and Ray and Miller (1994) among construction professionals and managers, as well as Montgomery et al (2003) and Houkes et al (2003) in their study on newspaper managers.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations